PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR DISCLOSURE) TERHADAP KINERJA KEUANGAN PERUSAHAAN - Ahmad Husnan; Sugeng Pamudji (Diponegoro Journal of Accounting, 2013)
This study aimed to examine the effect of Corporate Social Responsibility (CSR Disclosure) on corporate financial performance (return on assets, Return on Equity, Return on Sales and Current Ratio). In this study the company's financial performance is measured by using ROA, ROE, ROS and Current Ratio. Independent variables used in this study is the Corporate Social Responsibility with 79 disclosure according GRI, while the dependent variable is financial performance.Research samples were manufacturing companies listed on the Indonesia Stock Exchange (IDX) year study period 2008-2011. Data collected by the method of documentary and literature. The sample used was 156 companies during the four periods. This study uses linear regression to the data analysis.The results showed that the Corporate Social Responsibility (CSR) significantly influence the Return on Assets (ROA) and Return on Sales (ROS) but no significant effect on Return on Equity (ROE) and the Current Ratio.